Outcomes of Onlay Versus Sublay Mesh Hernioplasty for Ventral Abdominal Hernias - Saleem, Saadan; Naqvi, Syeda Rifaat Qamar; Luqman, Aimen; Razzaque, Hasnain; Khan, Mahlail Hassan; Haq, Qazi Tafheem Ul (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare surgical outcomes of Onlay versus Sublay technique of mesh hernioplasty among patients with ventral abdominal hernia. Study Design: Quasi-experimental study. Place and Duration of Study: Department of General Surgery, Combined Military Hospital, Rawalpindi Pakistan, from Oct 2021 to Mar 2022. Methodology: A total of 78 patients were selected, using convenience sampling, with reducible incisional, paraumbilical, supraumbilical or epigastric hernia, with a hernial defect measuring ≥2 cm. All preoperative parameters were recorded, and postoperative outcomes were monitored on follow-up at 2 weeks, 1 month and 2 months. Data was analyzed for statistical significance with p-value ≤0.05 being considered significant. Results: Open Onlay repair was performed on 41(52.6%) patients whereas the remaining 37(47.4%) cases had open Sublay mesh hernioplasty. The commonest ventral hernia types were paraumbilical 43(55.1%) and incisional 28(35.9%). Sublay procedure lasted for a significantly longer duration (p<0.001) but wound infections (OR: 1.67) and seromas (OR: 1.50) were slightly more frequent among the Onlay repair group (p=0.372 and p=0.521 respectively) whereas postoperative pain and wound dehiscence showed a similar rate of occurrence. Recurrence was more common after Sublay repair (14, 38%) as compared to Onlay 10(24.4%). Conclusion: The comparison between Onlay and Sublay mesh hernioplasty showed comparable surgical outcomes, with each technique presenting distinct advantages. While Sublay procedures took longer and had higher recurrence rates, they showed slightly lower wound complications. The choice of technique should be individualized based on patient factors and surgeon expertise.